Agricultural Economic Policy Model for Increasing Agricultural Digitalization Performance in Boyolali Regency - Santosa, Budi; Karunia Setyowati Suroto; Wulan Puji Lestari (IRDH International Journal of Technology, Agriculture and Natural Sciences, 2025)
Boyolali Regency is one of the areas in Central Java. Boyolali Regency itself has enormous potential in the agricultural sector. Agricultural economic policy is one of the things that is currently important for the government sector to formulate. This agricultural economic policy functions to bridge important strategies between farmers and the community and local government to determine the right steps in optimizing agricultural potential itself. This research aims to examine agricultural economic policy models for improving agricultural digitalization performance in Boyolali Regency. The method used in this research is an analytical descriptive method using primary and secondary data. Currently, the Boyolali Regency regional government is quite active in developing the agricultural sector, starting with infrastructure development, providing intensive care and assistance, and transforming into the digital sector. Digital development or transformation in the agricultural sector has a vital role in supporting the optimization of agricultural products in the Boyolali Regency. Even though this program has been carried out quite massively by the Boyolali regional government, it is important to continue to carry out further development. This digitalization also includes the use of appropriate and appropriate agricultural tools to make agricultural activities more effective.